Claudin-2 enhances human antibody-mediated complement-dependent cytotoxicity of porcine endothelial cells by modulating antibody binding and complement activation - Li, Weilong; Yang, Fang; Yang, Dexin; Song, Zhuoheng; Xu, Zigan; Wu, Jinmei; Li, Yanmei; Chen, Zixi; Chen, Peishan; Yu, Yeye; Xie, Ting; Yang, Cuishan; et al. (Frontiers in Immunology, 2025)
BackgroundImmune rejection represents a significant barrier to transplantation, especially in the context of xenotransplantation. Endothelial cells (ECs) derived from pigs serve as the initial barrier against the human immune system in xenotransplantation. Tight junction proteins are essential components of endothelial cell tight junctions; however, their role in xenotransplantation has been less thoroughly investigated. Claudin-2, a key tight junction protein, was investigated here for its role in human antibody-mediated complement-dependent cytotoxicity (CDC).MethodsUsing an in vitro model of human antibody-mediated CDC, we assessed the effect of Claudin-2 on porcine aortic endothelial cells (PAECs) and porcine iliac endothelial cells (PIECs). Claudin-2 expression was either knocked down or overexpressed in these cells. A flow cytometry assay was used to evaluate C3c, C9, and the C5b-9 deposition, as well as the extent of human IgM and IgG binding to PIECs. The mRNA levels of complement regulators (CD46, CD55, CD59, Factor H, Factor I) were quantified by real-time PCR.ResultsThe loss of Claudin-2 protected PAECs and PIECs from human antibody-mediated CDC, while the overexpression of Claudin-2 enhanced the cytotoxicity in PAECs and PIECs within the same model. Unexpectedly, the loss or overexpression of Claudin-2 did not influence the mRNA expression levels of complement regulators (CD46, CD55, CD59, Factor H, and Factor I). Importantly, the loss of Claudin-2 significantly decreased the deposition of the C5b-9 complex, commonly referred to as the membrane attack complex (MAC), whereas the overexpression of Claudin-2 enhanced the deposition of the C5b-9 complex, indicating that Claudin-2 facilitates complement activation. Furthermore, the loss of Claudin-2 resulted in a decrease in the deposition of C3c and C9 on PIECs. Moreover, Claudin-2 enhanced human antibody binding to porcine ECs, as evidenced by increased IgG and IgM binding.ConclusionOur findings indicate that Claudin-2 enhances the cytotoxicity of porcine ECs through modulating antibody binding and complement activation. The deficient of Claudin-2 in genetically modified pigs is likely to protect porcine ECs and enhance xenograft survival in pig-to-human organ or tissue xenotransplantation.